Early Detection of High Risk Pregnancy (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2017)
There are 30.939 pregnant women in Banyumas, with 6.206 cases referred due to high-risk pregnancies. Petahunan village in Pekuncen has the the highest incidence of high-risk pregnancies compared with other villages. The purpose of this study is to describe the implementation of early detection of high-risk pregnancies in Petahunan village, Pekuncen. This study used qualitative research methods with case study approach. Research instruments used in-depth interviews and focus group disscussion toward early detection of high-risk pregnancy issue. The informants were 7 people include pregnant women, health workers, midwives, head of village and village health forum chairman. The result showed only antenatal care implemented to detect high-risk pregnancy and no programs and community empowerment efforts in early detection of high-risk pregnancies.